Pattern of Production Relationship of Ponggawa - Petambak: The Pattern of Patron - Client Relationship (The Case of Ponggawa - Petambak Community at Babulu Laut Village, Babulu District, Pasir Regency, East Kalimantan Province) - Elly Purnamasari; Titik Sumantri; Lala M. Kolopaking (Forum Pasca Sarjana, 2002)
The relationship of Ponggawa - Petambak in fishfond aquaculture activity was a common phenomenon at many coastal village areas, particularly Babulu Laut Village (East Kalimantan). Although the relationship was considered to exploit petambak, but it had been institutionalized and hadn't been substituted with government formal institution. The aims of this research were (1) to identify interaction network pattern in fishfond aquaculture production and (2) to study the pattern of production relationship of ponggawa - petambak and social function in living of petambak community. Qualitative and quantitative approaches were integrated in this research. The research used survey and case study methods, applying full enumeration survey, observation and in-dept interview.